Method for preparing battery-grade lithium carbonate from electrolytic aluminum waste
The carbon in electrolytic aluminum scrap was removed by high-temperature calcination, and combined with two-stage leaching and two-stage impurity removal techniques, the problems of long processes and high energy consumption in the existing technology were solved, and the efficient lithium extraction of electrolytic aluminum scrap and the preparation of battery-grade lithium carbonate were achieved.
Patent Information
- Application Number
- CN202411750392.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, the lithium extraction method of electrolytic aluminum scrap has problems such as long process, high energy consumption and high pollution, especially for electrolytic aluminum scrap with high carbon and aluminum content, which is difficult to handle.
The carbon in the electrolytic aluminum scrap was removed by high-temperature calcination, followed by two-stage leaching and two-stage decomposition. By controlling the leaching and decomposition conditions, the leaching rate and purity of lithium were improved, and finally the battery-grade lithium carbonate was prepared by heating and freezing and crystallization.
It significantly shortens the process, reduces energy consumption and pollution, improves the extraction efficiency of lithium and the purity of the product, and reduces the processing cost.
Smart Images

Figure CN119706889A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of extraction and utilization of lithium-containing waste from electrolytic aluminum, and in particular to a method for preparing battery-grade lithium carbonate from electrolytic aluminum waste. Background Art
[0002] In recent years, the electric vehicle industry has been developing rapidly, driving the rapid development of the lithium-ion battery industry. The demand for lithium raw materials has continued to grow. Many companies have deployed lithium resources at home and abroad, developed lithium extraction technology, and are committed to the production of lithium carbonate. The price of lithium products has increased several times compared to before, which has also led to a rise in the price of lithium raw materials. At present, lithium carbonate is mainly prepared by extracting spodumene, lepidolite and other minerals or extracting lithium from salt lakes.
[0003] The development of the automobile and other industries has driven the growth of non-ferrous metal demand. The electrolytic aluminum industry has expanded production. The electrolytic aluminum waste slag contains a certain amount of lithium. The material has a high impurity content, especially high aluminum content, which is difficult to handle and has high processing costs. In recent years, the value of lithium raw materials in this material has been continuously paid attention to and studied.
[0004] In the prior art, Chinese patent CN105293536A discloses a method for extracting lithium from waste aluminum slag, wherein lithium-containing waste aluminum slag is subjected to a sulfation roasting reaction with concentrated sulfuric acid at 200-400°C, the roasting product is leached with water and then filtered to obtain a lithium-containing solution, the lithium-containing solution is added with sodium carbonate for alkaline hydrolysis at 20-40°C, the filter residue is added with water and then lime for causticization reaction, filtered, CO2 is introduced into the filtrate for carbonization reaction, and then filtered, washed, and dried to obtain battery-grade lithium carbonate. The product quality is excellent and the production is high in added value. This method uses a sulfation roasting process-water leaching precipitation-causticization-lithium precipitation to prepare battery-grade lithium carbonate, which has a long process, large reagent consumption, high energy consumption, and large pollution. Chinese patent CN109179457A discloses a method for extracting lithium from electrolytic aluminum waste residue, wherein the electrolytic aluminum waste residue is reacted with concentrated sulfuric acid to obtain a mixture A; (2) the mixture A is dissolved in water and filtered to obtain a filtrate B, calcium oxide is slowly added to the filtrate B, and the resulting solution is filtered to obtain a filter residue C and a filtrate D; (3) the filtrate D is heated and evaporated and concentrated, and the filtrate is further evaporated and concentrated after filtration to obtain a filtrate E, and the filtrate E is kept in a heated state; (4) a saturated sodium carbonate solution is added to the filtrate E to obtain a suspension F, and the suspension F is filtered to obtain a filter cake, and the filter cake is washed and dried to obtain a lithium carbonate product. This method uses waste residue from the electrolytic aluminum industry as raw material, which is lower in cost than lithium ore raw material, and is easy to extract. Other raw materials used in the extraction method are cheap and low in cost, and the resulting by-products can also be recycled, but this method has a long process and is difficult to treat electrolytic aluminum waste residue with high carbon and iron content. Summary of the invention
[0005] Therefore, in order to solve the problems of long process and high energy consumption in the prior art, the present invention proposes a method for preparing battery-grade lithium carbonate from electrolytic aluminum waste with high carbon and aluminum contents. The specific scheme is as follows:
[0006] A method for preparing battery-grade lithium carbonate from electrolytic aluminum waste, comprising the following steps:
[0007] Step 1: crushing the electrolytic aluminum waste with a carbon content of more than 50%, an aluminum content of 5-7 times that of lithium, and an iron content of at least 2 times that of lithium;
[0008] Step 2: calcining the crushed electrolytic aluminum waste at a high temperature of 550-1600°C for 0.5-5h to remove the carbon therein, then cooling and fine grinding, and the demagnetizer adsorbing the magnetic substances therein to obtain the decarbonized material;
[0009] Step 3: subjecting the decarbonized material to two-stage leaching, wherein the pH value of the first-stage leaching is controlled at 1.3-1.6, and filtering after the first-stage leaching to obtain a first-stage leaching liquid and a first-stage leaching residue; subjecting the first-stage leaching residue to a second-stage leaching, wherein the pH value of the second-stage leaching is controlled at 0.5-1.0, to obtain a second-stage leaching liquid and a second-stage leaching residue, and returning the second-stage leaching liquid to the first-stage leaching process;
[0010] Step 4: performing two-stage impurity removal, wherein the first-stage impurity removal process is: adding an oxidant to the first-stage leaching solution, then adding alkali to adjust the pH value to 4.5-5.0, and filtering to obtain a filtrate and a filter residue; the second-stage impurity removal process is: adding a decalcifying agent to the filtrate, then adding alkali to adjust the pH value to 12.0-13.0, and filtering to obtain a lithium-containing filtrate and an impurity filter residue;
[0011] Step 5: heating and concentrating the lithium-containing filtrate, and then freezing and crystallizing it to obtain a denitrified liquid;
[0012] Step 6: adding sodium carbonate solution to the denitrified liquid under heating conditions, precipitating and filtering to obtain crude lithium carbonate;
[0013] Step 7: Dissolve the crude sodium carbonate in pure water and introduce CO2 gas into the solution. When the crude sodium carbonate is completely dissolved, filter it precisely to obtain a lithium carbonate solution. Heat, crystallize, filter, wash and dry to obtain battery-grade lithium carbonate.
[0014] Furthermore, the composition and mass proportion of the electrolytic aluminum waste in step 1 are: lithium 1%-1.2%, aluminum 5.5-6.6%, sodium 9.5-10.0%, iron 2.2-2.5%, calcium 1.0-1.3%, magnesium 0.24-0.26%, silicon 2.5-2.9%, fluorine 6.0-6.5%, sulfur 0.14-0.15%, manganese <0.1%, carbon >50%, and the rest is water.
[0015] Furthermore, the size of the electrolytic aluminum waste after crushing in step 1 is 1-10 cm.
[0016] Furthermore, in the leaching process in step 3, the leaching agent is 98% sulfuric acid by mass, the leaching temperature is 60-90°C, the leaching time is 1-5h, the slurry liquid-solid ratio of water to carbon removal material in the first leaching is 3-10:1, the slurry liquid-solid ratio of the second leaching is 2-5:1, and the second leaching residue is washed and the washed liquid is returned to the first leaching.
[0017] Furthermore, in step 4, the oxidant in the first impurity removal process is air, the impurity removal temperature is 55-70°C, the alkali is a sodium hydroxide solution with a mass concentration of 5-30%, and the reaction time is 1-5h; the reaction time in the second impurity removal process is 1-5h, the decalcifying agent is oxalic acid, and the amount of decalcifying agent added is 0.06%-0.1% of the electrolytic aluminum waste.
[0018] Furthermore, the temperature of the freezing crystallization in step 5 is -10°C to 10°C.
[0019] Furthermore, the heating temperature in step 6 is 90-100°C.
[0020] Furthermore, in step 7, the mass ratio of pure water to crude lithium carbonate is 9-10:1, and the pressure of the introduced CO2 gas is 0.1-0.2 MPa.
[0021] Furthermore, the temperature of the heating crystallization in step 7 is 90-100°C.
[0022] Compared with the prior art, the present invention has the following advantages:
[0023] (1) The electrolytic aluminum waste slag of the present invention is first calcined at above 550°C to remove most of the carbon therein, and the lithium extraction processing capacity can be increased by almost one-fold. For the same reactor, the output can be doubled, the concentration of the lithium solution can be increased by about one-fold, and the amount of leached slag can be reduced by more than half, which greatly reduces the processing difficulty and cost, and improves the lithium recovery rate and processing efficiency.
[0024] (2) The present invention removes magnetic substances such as iron from the material through a demagnetizer, thereby reducing the material processing volume while removing most of the iron, reducing the amount of acid used in the leaching process, and maintaining the pH in a relatively low range during the leaching process, thereby ensuring sufficient leaching of lithium without having to consider the leaching of a large amount of iron. At the same time, the pH during the first stage of impurity removal is controlled not to exceed 5, so that the product of the first stage of impurity removal is mainly aluminum hydroxide, rather than a mixture of iron and aluminum precipitates. The relatively pure aluminum hydroxide precipitate residue can be used as a raw material for preparing aluminum and other aluminum compounds, such as alumina, cryolite, etc., or as a raw material for aluminum smelting after calcination.
[0025] (3) The present invention adopts two-stage normal pressure leaching to maximize the lithium leaching rate by controlling the leaching conditions. The lithium leaching rate can reach more than 99%. The leaching conditions are mild, without high temperature and high pressure conditions, with a high safety factor, low processing cost and easy operation.
[0026] (4) The lithium leaching solution of the present invention is subjected to two-stage impurity removal, wherein the first stage removes aluminum impurities, and the second stage removes other impurities such as manganese and calcium. The main products of the two stages of impurity removal are different and are processed separately. In addition, in the two-stage impurity removal process, oxalic acid is used as a decalcifying agent instead of conventional ion exchange resin, which can avoid the generation of excessive wastewater and the problem of easy scaling of ion exchange resin in sulfuric acid system. Calcium can be removed efficiently and the system operates smoothly.
[0027] (5) After the impurities are removed from the material, the lithium solution contains a high sodium content. Through low-temperature crystallization denitration, the denitration rate is high, and the sodium ion concentration in the lithium solution after denitration is low. The lithium solution after denitration is used to prepare battery-grade lithium carbonate by conventional methods, which has a simple process and low cost.
[0028] The method of the present invention does not require the addition of special reagents or the introduction of impurity elements, and can effectively extract lithium from electrolytic aluminum waste slag to prepare battery-grade lithium carbonate, with high added value and good economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The embodiments of the present invention are further described below with reference to the accompanying drawings, in which:
[0030] Figure 1 The process flow chart of the present invention is shown. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0032] A method for preparing battery-grade lithium carbonate from electrolytic aluminum waste, comprising the following steps:
[0033] Step 1: crushing the electrolytic aluminum waste with a carbon content of more than 50%, an aluminum content of 5-7 times the lithium content, and an iron content of at least 2 times the lithium content, and the size of the crushed electrolytic aluminum waste is 1-10cm; lithium 1%-1.2%, aluminum 5.5-6.6%, sodium 9.5-10.0%, iron 2.2-2.5%, calcium 1.0-1.3%, magnesium 0.24-0.26%, silicon 2.5-2.9%, fluorine 6.0-6.5%, sulfur 0.14-0.15%, manganese <0.1%, carbon>50%, and the rest is water.
[0034] Step 2: calcining the crushed electrolytic aluminum waste at a high temperature of 550-1600°C for 0.5-5h to remove the carbon therein, then cooling and fine grinding, and the demagnetizer adsorbing the magnetic substances therein to obtain the decarbonized material;
[0035] Step 3: subjecting the decarbonized material to two-stage leaching, wherein the pH value of the first stage leaching is controlled at 1.3-1.6, and filtering after the first stage leaching to obtain a first stage leaching solution and a first stage leaching residue; subjecting the first stage leaching residue to two-stage leaching, wherein the pH value of the second stage leaching is controlled at 0.5-1.0, to obtain a second stage leaching solution and a second stage leaching residue, and returning the second stage leaching solution to the first stage leaching process; the slurry liquid-solid ratio in the leaching process is 3-10:1, the leaching agent is 98% sulfuric acid by mass, the leaching temperature is 60-90°C, and the leaching time is 1-5h; the liquid-solid ratio of the second stage leaching is 2-5:1, the leaching time is 1-5h, and the second stage leaching residue is washed and the washed liquid is returned to the first stage leaching.
[0036] Step 4: perform two-stage impurity removal, wherein the first stage impurity removal process is: add an oxidant to the first stage leaching solution, then add alkali to adjust the pH value to 4.5-5.0, and filter to obtain a filtrate and a filter residue; the oxidant in the first stage impurity removal process is air, the impurity removal temperature is 55-70°C, the alkali is a sodium hydroxide solution with a mass concentration of 5-30%, and the reaction time is 1-5h;
[0037] Al2(SO4)3+6NaOH→3Na2SO4+2Al(OH)3↓
[0038] The second stage impurity removal process is: add a decalcifying agent to the filtrate, then add alkali to adjust the pH value to 12.0-13.0, and filter to obtain a lithium-containing filtrate and impurity filter residue; the reaction time in the second stage impurity removal process is 1-5h, the decalcifying agent is oxalic acid, and the amount of the decalcifying agent added is 0.06%-0.1% of the electrolytic aluminum waste.
[0039] Mn 2+ +2NaOH→2Na + +Mn(OH)2↓
[0040] H2C2O4+Ca 2+ →CaC2O4↓+2H +
[0041] Mg 2+ +2NaOH→2Na + +Mg(OH)2↓
[0042] Step 5: Heat and concentrate the lithium-containing filtrate, and then freeze and crystallize it to obtain a denitrified liquid; the temperature of the freeze and crystallization is -10°C-10°C to remove sodium sulfate.
[0043] Step 6: Add sodium carbonate solution to the denitrified liquid under heating conditions, and filter the precipitate to obtain crude lithium carbonate; the heating temperature is 90-100°C.
[0044] Li2SO4+Na2CO3→Li2CO3↓+2Na2SO4
[0045] Step 7: Dissolve the crude sodium carbonate in pure water and introduce CO2 gas into the solution. When the crude sodium carbonate is completely dissolved, filter it accurately to obtain a lithium carbonate solution. Heat it for crystallization, filter it, wash it, and dry it to obtain battery-grade lithium carbonate. The mass ratio of pure water to crude lithium carbonate is 9-10:1, the pressure of the CO2 gas introduced is 0.1-0.2MPa, and the temperature of heating crystallization is 90-100℃.
[0046] The specific embodiments are as follows:
[0047] The electrolytic aluminum waste slag used in the following examples is in the form of hard blocks with a carbon content exceeding 50%. The main components of the material are shown in Table 1.
[0048] Table 1 Composition and content of electrolytic aluminum waste slag
[0049]
[0050] The raw material contains 1.17% lithium, of which the aluminum content is relatively high, 6.441, which is 5.5 times the lithium content, and the iron content is about 2 times the lithium content. The silicon content of this material is not high, but the fluorine content is relatively high, and it also contains a small amount of sulfur and more than 50% carbon.
[0051] Example 1
[0052] (1) 1500 g of electrolytic aluminum waste is roughly crushed into small pieces of about 1-10 cm.
[0053] (2) Carbon removal: 1000 g of the crushed material was placed in a calcining furnace and heated at 550°C for 5 h, then cooled, finely ground and sieved through a 60-mesh sieve for later use, and the magnetic material was adsorbed by a demagnetizer to obtain a carbon-removed material.
[0054] (3) The decarbonizing material and water are mixed and stirred evenly at a liquid-to-solid ratio of 10:1, 98% sulfuric acid is added, and the mixture is heated at 80°C in a water bath for a first leaching, sulfuric acid is added to adjust the pH value to 1.3, the mixture is leached for 1 hour, and the mixture is filtered after leaching to obtain a first leaching solution and a first leaching residue, the first leaching residue is slurried with sulfuric acid at a liquid-to-solid ratio of 2:1 and then subjected to a second leaching, the pH value at the leaching end point is 0.8, the mixture is leached for 1 hour, and the mixture is filtered after leaching to obtain a second leaching solution and a second leaching residue, the second leaching residue is washed twice, the first leaching solution is subjected to subsequent treatment, and the washing water of the second leaching solution and the second leaching residue is combined for a first leaching slurry or leaching; the leaching kettle is connected to an absorption device, the absorption liquid is pure water, and the HF gas generated during the leaching process is absorbed; the lithium leaching rate is 98.78%, the iron leaching rate is 99.05%, and the aluminum leaching rate is 29.77%.
[0055] (4) Impurity removal: The first-stage leachate is subjected to two-stage impurity removal. The first-stage impurity removal is as follows: air is introduced into the first-stage leachate for 20 minutes, and then 5% sodium hydroxide is added to adjust the pH value to 4.5. The reaction temperature is maintained at 60°C and the reaction time is 4 hours. The filtrate and filter residue are obtained by filtration. The filter residue is slurried and washed twice. The filtrate is subjected to two-stage impurity removal. 1 g of decalcifying agent oxalic acid is added and then 5% sodium hydroxide is added to adjust the pH value to 12.0. The reaction time is 3 hours. The lithium-containing filtrate and impurity filter residue are obtained by filtration, and the filter residue is stored.
[0056] (5) Concentration and denitrification: The lithium-containing filtrate is heated and concentrated, and then cooled to 5°C, 0°C, and -5°C for three-stage freezing and crystallization of sodium sulfate to obtain a denitrified liquid.
[0057] (6) Lithium precipitation: Sodium carbonate is added to the denitrified liquid at 90°C to precipitate crude lithium carbonate.
[0058] (7) Add 10 times the mass of pure water to the crude lithium carbonate to dissolve it, then introduce CO2 gas at a pressure of 0.1 MPa, and accurately filter after all the lithium carbonate is dissolved to obtain a lithium carbonate solution. Heat the lithium solution to a slightly boiling temperature (90-100°C) for crystallization, filter, wash, and dry to obtain battery-grade lithium carbonate.
[0059] Example 2
[0060] (1) 5000g of electrolytic aluminum waste is roughly crushed into small pieces of about 5-10cm.
[0061] (2) 4000 g of the coarsely crushed material is placed in a crucible and placed in a calcining furnace at a calcination temperature of 1000°C for 3 hours. The material is finely ground and passed through a 100-mesh sieve for later use, and a demagnetizer is used to absorb the magnetic material to obtain a decarbonized material.
[0062] (3) The carbon removal material and water are mixed and stirred evenly at a liquid-to-solid ratio of 5:1, 98% sulfuric acid is added, and the mixture is heated in a water bath at 70°C for a first leaching, sulfuric acid is added to adjust the pH value to 1.5, the leaching is carried out for 2.5 hours, and the leaching is filtered after leaching to obtain a first leaching solution and a first leaching residue, the first leaching residue is slurried with sulfuric acid at a liquid-to-solid ratio of 5:1 and then subjected to a second leaching, the pH value at the leaching end point is 0.5, the leaching is carried out for 2.5 hours, and the leaching is filtered after leaching to obtain a second leaching solution and a second leaching residue, the second leaching residue is washed twice, the first leaching solution is subjected to subsequent treatment, and the washing water of the second leaching solution and the second leaching residue is combined for a first leaching slurry or leaching; the leaching kettle is connected to an absorption device, the absorption liquid is pure water, and the HF gas generated during the leaching process is absorbed; the lithium leaching rate is 98.44%, the iron leaching rate is 99.25%, and the aluminum leaching rate is 31.25%.
[0063] (4) Impurity removal: The first-stage leachate is subjected to two-stage impurity removal. The first-stage impurity removal is as follows: air is introduced into the first-stage leachate for 30 minutes, 20% sodium hydroxide is added to adjust the pH value to 5.0, the reaction temperature is maintained at 70° C., the reaction time is 1 hour, and a filtrate and a filter residue are obtained by filtration. The filter residue is slurried and washed twice, and the filtrate is subjected to two-stage impurity removal. 3 g of decalcifying agent oxalic acid is added, and then 20% sodium hydroxide is added to adjust the pH value to 12.0. The reaction time is 1 hour, and a lithium-containing filtrate and an impurity filter residue are obtained by filtration. The filter residue is stored;
[0064] (5) Concentration and denitrification: The lithium-containing filtrate is heated and concentrated, and sodium sulfate is frozen and crystallized in three stages to obtain the denitrified liquid.
[0065] (6) Lithium precipitation: Sodium carbonate is added to the denitrified liquid at 95°C to precipitate crude lithium carbonate.
[0066] (7) Add 9 times the mass of pure water to the crude lithium carbonate to dissolve it, then introduce CO2 gas at a pressure of 0.2 MPa. After all the lithium carbonate is dissolved, fine filtration is performed to obtain a lithium carbonate solution. The lithium solution is heated to a slightly boiling temperature (90-100°C) for crystallization, and filtered, washed, and dried to obtain battery-grade lithium carbonate.
[0067] Example 3
[0068] (1) 16 kg of electrolytic aluminum waste is roughly crushed into small pieces of about 5-10 cm.
[0069] (2) 15 kg of the coarsely crushed material is placed in a crucible and placed in a calcining furnace at a calcination temperature of 1600°C for 0.5 h. The material is finely ground through a 200-mesh sieve for later use, and a demagnetizer is used to absorb the magnetic material to obtain a decarbonized material.
[0070] (3) The carbon removal material and water are mixed and stirred evenly at a liquid-to-solid ratio of 3:1, 98% sulfuric acid is added, and the mixture is heated at 90°C in a water bath for a first leaching, sulfuric acid is added to adjust the pH value to 1.3, the leaching is carried out for 5 hours, and the first leaching solution and the first leaching residue are obtained. The first leaching residue is slurried with sulfuric acid at a liquid-to-solid ratio of 3:1 and then subjected to a second leaching, the pH value at the leaching end point is 1.0, the leaching is carried out for 5 hours, and the second leaching solution and the second leaching residue are obtained. The second leaching residue is washed twice, the first leaching solution is subjected to subsequent treatment, and the washing water of the second leaching solution and the second leaching residue is combined for a first leaching slurry or leaching; the leaching kettle is connected to an absorption device, and the absorption liquid is pure water to absorb the HF gas generated during the leaching process; the lithium leaching rate is 98.11%, the iron leaching rate is 98.85%, and the aluminum leaching rate is 25.65%.
[0071] (4) Impurity removal: The first-stage leachate is subjected to two-stage impurity removal. The first-stage impurity removal is as follows: air is introduced into the first-stage leachate for 60 minutes, and then 30% sodium hydroxide is added to adjust the pH value to 5.0. The reaction temperature is maintained at 70°C and the reaction time is 5 hours. The filtrate and filter residue are obtained by filtration. The filter residue is slurried and washed twice. The filtrate is subjected to two-stage impurity removal. 15g of decalcifying agent oxalic acid is added and then 30% sodium hydroxide is added to adjust the pH value to 13.0. The reaction time is 5 hours. The lithium-containing filtrate and impurity filter residue are obtained by filtration, and the filter residue is stored.
[0072] (5) Concentration and denitrification: The lithium-containing filtrate is heated and concentrated, and sodium sulfate is frozen and crystallized in three stages to obtain the denitrified liquid.
[0073] (6) Lithium precipitation: Sodium carbonate is added to the denitrified liquid at 98°C to precipitate crude lithium carbonate.
[0074] (7) Add 10 times the mass of pure water to the crude lithium carbonate to dissolve it, then introduce CO2 gas at a pressure of 0.2 MPa, and then accurately filter after all the lithium carbonate is dissolved to obtain a lithium carbonate solution. The lithium solution is heated to a slightly boiling temperature (90-100°C) for crystallization, and filtered, washed, and dried to obtain battery-grade lithium carbonate.
[0075] Table 1 Composition of the final lithium carbonate product in the embodiment
[0076]
[0077] Some exemplary embodiments of the present invention are described above. It can be understood that the above embodiments are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention. The features in these embodiments can be recombined in a suitable manner, and the scheme obtained thereby is still within the protection scope required by the present invention. Based on the above embodiments, all other embodiments obtained by those skilled in the art without making creative work, that is, all modifications, equivalent substitutions and improvements made within the spirit and principles of this application, fall within the protection scope required by the present invention.
Claims
1. A method for preparing battery-grade lithium carbonate from electrolytic aluminum waste, characterized in that: The following steps are involved: Step 1: crushing the electrolytic aluminum waste with a carbon content of more than 50%, an aluminum content of 5-7 times that of lithium, and an iron content of at least 2 times that of lithium; Step 2: calcining the crushed electrolytic aluminum waste at a high temperature of 550-1600°C for 0.5-5h to remove the carbon therein, then cooling and fine grinding, and the demagnetizer adsorbing the magnetic substances therein to obtain the decarbonized material; Step 3: subjecting the decarbonized material to two-stage sulfuric acid leaching, wherein the pH value of the first stage leaching is controlled at 1.3-1.6, and filtering after the first stage leaching to obtain a first stage leaching solution and a first stage leaching residue; subjecting the first stage leaching residue to a second stage leaching, wherein the pH value of the second stage leaching is controlled at 0.5-1.0, to obtain a second stage leaching solution and a second stage leaching residue, and returning the second stage leaching solution to the first stage leaching process; Step 4: performing two-stage impurity removal, wherein the first-stage impurity removal process is: adding an oxidant to the first-stage leaching solution, then adding alkali to adjust the pH value to 4.5-5.0, and filtering to obtain a filtrate and a filter residue; the second-stage impurity removal process is: adding a decalcifying agent to the filtrate, then adding alkali to adjust the pH value to 12.0-13.0, and filtering to obtain a lithium-containing filtrate and an impurity filter residue; Step 5: heating and concentrating the lithium-containing filtrate, and then freezing and crystallizing it to obtain a denitrified liquid; Step 6: adding sodium carbonate solution to the denitrified liquid under heating conditions, precipitating and filtering to obtain crude lithium carbonate; Step 7: Dissolve the crude sodium carbonate in pure water and introduce CO2 gas into the solution. When the crude sodium carbonate is completely dissolved, filter it precisely to obtain a lithium carbonate solution. Heat, crystallize, filter, wash and dry to obtain battery-grade lithium carbonate.
2. The method for preparing battery-grade lithium carbonate from electrolytic aluminum waste according to claim 1, characterized in that: The composition and mass proportion of the electrolytic aluminum waste in step 1 are: lithium 1%-1.2%, aluminum 5.5-6.6%, sodium 9.5-10.0%, iron 2.2-2.5%, calcium 1.0-1.3%, magnesium 0.24-0.26%, silicon 2.5-2.9%, fluorine 6.0-6.5%, sulfur 0.14-0.15%, manganese <0.1%, carbon>50%, and the rest is water.
3. The method for preparing battery-grade lithium carbonate from electrolytic aluminum waste according to claim 1, characterized in that: The size of the electrolytic aluminum scrap after crushing in step 1 is 1-10 cm.
4. The method for preparing battery-grade lithium carbonate from electrolytic aluminum waste according to claim 1, characterized in that: In the leaching process in step 3, the leaching agent is 98% sulfuric acid by mass, the leaching temperature is 60-90° C., the leaching time is 1-5 hours, the slurry liquid-solid ratio of water to carbon removal material in the first leaching is 3-10:1, the slurry liquid-solid ratio of the second leaching is 2-5:1, and the second leaching residue is washed and the washed liquid is returned to the first leaching.
5. The method for preparing battery-grade lithium carbonate from electrolytic aluminum waste according to claim 1, characterized in that: In step 4, the oxidant in the first stage of impurity removal is air, the impurity removal temperature is 55-70°C, the alkali is a sodium hydroxide solution with a mass concentration of 5-30%, and the reaction time is 1-5h; the reaction time in the second stage of impurity removal is 1-5h, the decalcifying agent is oxalic acid, and the amount of decalcifying agent added is 0.06%-0.1% of the electrolytic aluminum waste.
6. The method for preparing battery-grade lithium carbonate from electrolytic aluminum waste according to claim 1, characterized in that: The temperature of the freezing crystallization in step 5 is -10°C to 10°C.
7. The method for preparing battery-grade lithium carbonate from electrolytic aluminum waste according to claim 1, characterized in that: The heating temperature in step 6 is 90-100°C.
8. The method for preparing battery-grade lithium carbonate from electrolytic aluminum waste according to claim 1, characterized in that: In step 7, the mass ratio of pure water to crude lithium carbonate is 9-10:1, and the pressure of the introduced CO2 gas is 0.1-0.2MPa.
9. The method for preparing battery-grade lithium carbonate from electrolytic aluminum waste according to claim 1, characterized in that: The temperature of heating crystallization in step 7 is 90-100°C.
Citation Information
Patent Citations
Method of extracting lithium from electrolytic aluminium waste residues
CN105293536A
Method for extracting lithium from electrolytic aluminum waste residues
CN109179457A
Cited By
Method for extracting lithium from solid waste of aluminum electrolysis cell
CN121874503A